1,2-dihydrophosphete: A platform for the molecular engineering of electroluminescent phosphorus materials for light-emitting devices - Chen, Hui (2014)
The discovery and molecular engineering of novel electroluminescent materials is still a challenge in optoelectronics. In this work, the development of new π-conjugated oligomers incorporating a dihydrophosphete skeleton is reported. Variation of the substitution pattern of 1,2-dihydrophosphete derivatives and chemical modification of their P atoms afford thermally stable derivatives, which are suitable emitters to construct organic light-emitting diodes (OLEDs). The optical and electrochemical properties of these new P-based oligomers have been investigated in detail and are supported by DFT calculations. The OLED devices exhibit good performance and current-independent CIE coordinates.